COMPARISON OF PROTHROMBIN TIME AND ACTIVATED PARTIAL THROMBOPLASTIN TIME BETWEEN PATIENTS WITH DIABETES MELLITUS AND DIABETICS WITH HYPERTENSION - P.KRISHNA CHAITANYA; SUCHITRA KAVURI; K.AMBIKA DEVI (International Journal of Pharma and Bio Sciences, 2014)
Uncontrolled Diabetes Mellitus Causes both microangiopathy leading to diabetic nephropathy & retinopathy and macroangiopathy leading to coronary heart diseases & also diabetic neuropathy. Hypertension itself is characterized by arteriosclerosis. To assess the coagulation status, we measured PT & APTT in these cases. A 52 Known Type II diabetic patients with hypertension, 32 known Type II Diabetes Mellitus patients & 30 controls were included in the study. Both PT & APTT were measured on CA-50 Sysmex Coagulation Analyzer. The FBS & PPBS were estimated on Humastar-300 complete Auto analyzer. BMI was calculated for all the subjects. The PT was prolonged in Group B (14.86538 + 0.12290 ) than controls (13.83333 + 0.08419) ,p = 0.0000001 and Group A(13.40 + 1.29) ,p = 0.0000001. The APTT was prolonged in Group B (34.53846 + 0.27933 ) than controls (30.13333 + 0.32424) p = 0.0000001 and Group A(30.81 + 2.40) ,p = 0.0000001 respectively. The FBS was increased in cases than controls ( p = 0.0000001 ). The PPBS was also increased in cases than controls ( p = 0.0000001). The BMI for Group A (26.55 + 3.2) Group B (26.9615 + 2.6515) and for controls (25.05 + 2.7268). This study showed Prolonged PT and APTT in diabetes mellitus with hypertension. Abnormal PT & APTT are the indications of altered activity or absence or decreased levels of clotting factors of intrinsic & extrinsic coagulation pathways respectively. The BMI value indicates that cases are overweight. PT & APTT should be checked in such cases prior to any surgery.